2019
DOI: 10.1111/jcal.12405
|View full text |Cite
|
Sign up to set email alerts
|

Predicting students' knowledge after playing a serious game based on learning analytics data: A case study

Abstract: Serious games have proven to be a powerful tool in education to engage, motivate, and help students learn. However, the change in student knowledge after playing games is usually measured with traditional (paper) prequestionnaires–postquestionnaires. We propose a combination of game learning analytics and data mining techniques to predict knowledge change based on in‐game student interactions. We have tested this approach in a case study for which we have conducted preexperiments–postexperiments with 227 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 24 publications
3
29
0
4
Order By: Relevance
“…The effect of the interaction between the player and the use of the PCs was reflected further in science learning outcomes, such that the less characters of the first defence line were used, the more characters of the third defence line were used and the better were the science learning outcomes. The results aligned with previous studies by Alonso‐Fernández et al (2020), Cheng, Lin, and She (2015) and Cheng, She, and Annetta (2015), supporting the value of the interactions with game characters in predicting game‐based learning outcomes. These together implied that Humunology 's game design is consistent with the actual immune mechanisms, so that the gameplay behaviours represent scientific facts well and are effective for learning overall.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The effect of the interaction between the player and the use of the PCs was reflected further in science learning outcomes, such that the less characters of the first defence line were used, the more characters of the third defence line were used and the better were the science learning outcomes. The results aligned with previous studies by Alonso‐Fernández et al (2020), Cheng, Lin, and She (2015) and Cheng, She, and Annetta (2015), supporting the value of the interactions with game characters in predicting game‐based learning outcomes. These together implied that Humunology 's game design is consistent with the actual immune mechanisms, so that the gameplay behaviours represent scientific facts well and are effective for learning overall.…”
Section: Discussionsupporting
confidence: 90%
“…Their another study extracted gameplay data, such as whether the game has been completed, game scores, the interactions with game elements and so forth to build models for predicting knowledge acquisition. The results demonstrated that gameplay data can be effective for accurately predicting student learning, and the number of interactions with game character was one best predictor (Alonso‐Fernández et al, 2020). Cheng, Lin, and She (2015) created an educational game for the students to learn the mechanism of biological evolution by manipulating a team of the PCs to compete with NPCs controlled by the computer.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have examined knowledge acquisition with game‐based learning environments using a range of data channels such as gameplay behavior traces (eg, Alonso‐Fernández et al ., 2019; Alonso‐Fernández, Martínez‐Ortiz, Caballero, Freire, & Fernández‐Manjón, 2020; Taub et al ., 2017), facial expressions of emotions (eg, Lane & D’Mello, 2019; Taub, Sawyer, Smith, et al ., 2020), performance measures (eg, pre/posttest scores; Dever & Azevedo, 2019), self‐report measures (eg, Cloude, Taub, Lester, & Azevedo, 2019) and eye gaze (eg, Dever, Wiedbusch, & Azevedo, 2019; Gomes, Yassine, Worsley, & Blikstein, 2013; Lee, Donkers, Jarodzka, & van Merriënboer, 2019; Tsai, Huang, Hou, Hsu, & Chiou, 2016). A noteworthy study used gameplay behavior traces to model students’ self‐reported interest during game‐based learning (Sawyer, Rowe, Azevedo, & Lester, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Simva has helped us in different validation experiments to simplify data collection and processing, saving us time and automating some of the processes that were most prone to errors. We have used Simva with more than 1000 students and 3 different serious games: in Conectado [2] we linked questionnaires with the collected LA data; in First Aid Game [8] we linked together data from two experiments over time; and in the 15 Objects test [9] we used the metadata feature to include the information of which of the two versions of the game each student was using.…”
Section: Discussionmentioning
confidence: 99%